2019
DOI: 10.1002/nau.23941
|View full text |Cite
|
Sign up to set email alerts
|

Predicting continence decline in institutionalized older people: A longitudinal analysis

Abstract: Aims To verify the incidence of urinary continence decline and the probability of maintaining urinary continence, as well as identify the prognostic factors of urinary continence decline in institutionalized older people. Methods A 2‐year longitudinal study (with five 6‐month waves) was conducted with subjects ≥60 years old who lived in 10 nursing homes in the city of Natal‐RN (Brazil). Urinary incontinence was assessed by the Minimum Data Set version 3.0. Sociodemographic, institution‐related and health‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…9 10 However, UI is a geriatric syndrome that represents an indicator of frailty and quality of healthcare, as well as a risk factor for pressure ulcers, falls, fractures and even urinary sepsis or death. [11][12][13] NH residents are the least physically active of all older adults and spend most of their awake time sedentary. 14 15 Doing regular physical activity (PA) limits the development and progression of most prevalent chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…9 10 However, UI is a geriatric syndrome that represents an indicator of frailty and quality of healthcare, as well as a risk factor for pressure ulcers, falls, fractures and even urinary sepsis or death. [11][12][13] NH residents are the least physically active of all older adults and spend most of their awake time sedentary. 14 15 Doing regular physical activity (PA) limits the development and progression of most prevalent chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This health professionals' perception is in line with data from the OsoNaH project comparing the pre‐pandemic baseline assessment versus the posterior 12‐month follow‐up, showing that 54.4% and 30.4% of residents suffered from functional and continence decline, respectively (pending publication). The association of low functional capacity as a risk factor for continence decline has been clearly established in several longitudinal studies conducted in NHs of different countries 22 …”
Section: Discussionmentioning
confidence: 96%
“…The association of low functional capacity as a risk factor for continence decline has been clearly established in several longitudinal studies conducted in NHs of different countries. 22 More recently, new evidence shows the effects of lockdown on cognitive capacity, depression, anxiety, frailty and disability. 20 The infection control measures led to social isolation and loneliness, psychosocial health issues that are associated with fatigue, physical inactivity, cognitive decline, depression, and early mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors affirmed that could be due to the difficulty getting to the bathroom or multi-factorial causes of both immobility and incontinence [37]. Similarly, Jerez-Roig and colleagues [38] found that disability and functional decline are significant predictors of urinary continence decline after two years in a sample of institutionalized older adults. However, Krause et al (2010) [39] showed that 6-min walk test, chair stand test, and test of sit-and-reach were not significant predictors of urinary incontinence [39].…”
Section: Discussionmentioning
confidence: 99%